The journey of Jephthah"s daughter: On spatial cognition, body and language in Judges 11:37 - Lamprecht, Adriaan (HTS teologiese studies, 2021)
The traditional literal interpretation of the text in Judges 11:37 shows exceptional variation in topographic depiction. The literal interpretation of Driver, published in Zeitschrift für die Alttestamentliche Wissenschaft, is an example. From a linguistic perspective, no attention was paid whatsoever to the relation of interiority between an objective body and an objective space. This article proposes a cognitive semantic perspective and argues that the motion-path verb ירד (yrd) in Judges 11:37 carries a metaphorical meaning, and the linguistic processing, that is, the metaphorical mapping of the image schematic structure of CHANGE (up-down) as the source domain onto that of BEHAVIOUR as the target domain, involving activation of cultural spatial and bodily systems. With this background in mind, Judges 11:37 represents a new understanding for similar UP-DOWN image schemas applied in the Hebrew Bible.Contribution: This article contributes to the understanding of the apparent ‘inexact’ sense of the use of ירד (yrd) in Judges 11:37.